The Process of Promotion - Bolick, Hannah (East Carolina University, 2021)
This is not really an honors thesis but a formal write-up of our group honors project. The process we used to complete this project is called Human Centered Design. It is a formula that uses principles of design thinking and human empathy to produce solutions to grand challenges that keep people at the forefront of the mind. It is a technique that embraces failure, questions often, is comfortable with change, and has a bias toward action. According to the IDEO’s Design Kit website, the three basic methods of the human centered design process are Inspiration, Ideation, and Implementation (“Methods”). We worked through this process during our time in the Honors courses to solve the problem of the struggling arts community in Greenville. We began by conducting copious numbers of interviews on our topic. We found, in short, that there are artists in Greenville who want to practice their craft and that there is an interest in the community in both the performing and visual arts but there is a disconnect between these two groups. Therefore, our core mission is to connect artists with audiences for the purpose of enriching the arts scene in Greenville. We wanted to become promoters of the arts. Our original core mission was to connect the arts community on campus with the greater Greenville arts community. We later broadened our mission to allow for broader impact. We did a prototyping event and each time a version of our project failed, we pivoted to a new iteration of our product. Each time we did so, we were sure to re-center to our core mission to make sure that the people we were trying to help were continually in mind as we reshaped our plan. The idea is to have bias toward action, doing and evaluating the results.
Keywords: Human Centered Design; Showboost; art; artist; music; musician; promotion